Adapting HYDRUS-1D to simulate the transport of soil water isotopes with evaporation fractionation. (September 2021) - Zhou, Tiantian; Šimůnek, Jirka; Braud, Isabelle
Abstract: Ecohydrological processes are often evaluated by studying the fate of stable water isotopes. However, isotopic fractionation during evaporation is often ignored or simplified in current models, resulting in simulation errors that may be propagated into practical applications of stable isotope tracing. In this study, we adapted and tested the HYDRUS-1D model, a numerical model widely used to simulate variably-saturated water flow and solute transport in porous media, by including an option to simulate isotope fate and transport while accounting for evaporation fractionation. The numerical results obtained by the adapted model were in excellent agreement with existing analytical solutions. Additional plausibility tests and field evaluation further demonstrated the adapted model's accuracy. A simple particle tracking algorithm was also implemented to calculate soil water's transit times and further validate the modified model's results. Transit times calculated by the particle tracking module (PTM) were similar to those estimated by the isotope peak displacement method, validating the applicability of the PTM. The developed model represents a comprehensive tool to numerically investigate many important research problems involving isotope transport processes in the critical zone. Highlights: A new isotope transport module that considers evaporation fractionation was developed for HYDRUS-1D. A water flow-based particle tracking algorithm was also implemented to calculate the transit time. These new modules can be operated while using HYDRUS-1D software features, such as its user-friendly GUI.